Student Perceptions on Service Quality of Higher Education: An Empirical Study - Rahayu, Fatik; Murtanto, Murtanto; Ekasari, Ayu (Accounting Department,, 2007)
Educational literatures suggest that there is mounting pressure from customers of higher education to close the gap between their expectation of institutional performance and the actual performance (Widrick et al., 2002; Pariseau and Mc Daniel, 1997; Shank et al., 1995). Therefore, it is imperative that higher educations actively monitor the quality of their service. This study deals with measuring the service quality in higher education. The service quality of higher education in this research is defined as the difference between perception of performance and expectation of higher education. The instrument from Shank et al. (1995) was used in this study. The questionnaires were sent to students from some big universities in Jakarta. The t test was used to analysis the data